The Burden of Shading and Location on the Sustainability of South African Solar Home System Program. (August 2015) - Azimoh, Chukwuma Leonard; Klintenberg, Patrik; Wallin, Fredrik; Karlsson, Björn
Abstract: Most contributions on the issues of sustainability of rural electrification projects have focused on the technology and business models used to drive the projects. The issues of user education and environmental impact on the technology have received little attention. This has resulted in short lives of many rural electrification projects after commissioning. The usage pattern of solar home system (SHS) by most users that placed their solar panels close to obstructing objects, which results in shading of the panels, and location of households in the concession areas of South African SHS program is affecting the performances of SHS. The non-optimal use of SHS is as a result of lack of user education. Therefore this paper reports on the impact of location and shading of panels on the economics and technical performance of SHS. The study is achieved by investigating the performances of a 75 WP solar panel operated from two sites in South Africa (Upington in Northern Cape Province and Thlatlaganya in Limpopo Province), the performances of an optimized shaded SHS and a non-shaded one is also investigated. The results shows that both activities compromises the performance of the systems, the energy output of a solar panel located at Upington is increased by 10% and the state of charge of the battery (SOC) increased by 7%, compared to the panel situated at Thlatlaganya village. Also the life span of the battery is increased by about one year. The SOC of the partially shaded SHS is reduced by 22% and loss of power to the load increased by 20%. The geographical location of the SHS concession areas in South Africa and lack of adherence to the manufacturer's installation specification affects the economics of SHS and the energy output vis-à-vis the sustainability of the program due to reduction in life cycle of the batteries.